Three years ago, the average age of X, Y and Z was 27 years and that of Y and Z, 5 years ago was 20 years. X’s present age is:

 

  • Option 1)

     

    30 years

     

  • Option 2)

     

    25 years

     

  • Option 3)

     

    40 years

     

  • Option 4)

     

    48 years

     

  • Option 5)

     

    35 years

     

Answers (1)

If three years ago, the average age of X, Y and Z was 27 years and that of Y and Z, 5 years ago was 20 years. so the X’s present age is:

(x-3)+(y-3)+(z-3) = 3*27
x+y+z= 81+9=90...........(i)
(y-5)+(z-5)=2*20
y+z=40+10=50.........(ii)
From (i) & (ii)
x= 40 years

 

Exams
Articles
Questions